A nucleic acid detection assay combining reverse transcription recombinase-aided amplification with a lateral flow dipstick for the rapid visual detection of porcine deltacoronavirus. Issue 1 (31st December 2022) - Zeng, Jianyu; Wang, Wenlong; Zhou, Lei; Ge, Xinna; Han, Jun; Guo, Xin; Chen, Yanhong; Zhang, Yongning; Yang, Hanchun
ABSTRACT: Porcine deltacoronavirus (PDCoV) is an emerging enteropathogen causing severe diarrhoea, dehydration, and death in nursing piglets and enormous economic losses for the global swine industry. Furthermore, it can infect multiple animal species including humans. Therefore, a rapid, definitive diagnostic assay is required for the effective control of this zoonotic pathogen. To identify PDCoV, we developed a nucleic acid detection assay combining reverse transcription recombinase-aided amplification (RT-RAA) with a lateral flow dipstick (LFD) targeting the highly conserved genomic region in the ORF1b gene. The RT-RAA-LFD assay exhibited good PDCoV detection reproducibility and repeatability and could be completed within 11 min. Ten minutes at 40 °C was required for nucleic acid amplification and 1 min at room temperature was needed for the visual LFD readout. The assay specifically detected PDCoV and did not cross-react with any other major swine pathogens. The 95% limit of detection (LOD) was 3.97 median tissue culture infectious dose PDCoV RNA per reaction. This performance was comparable to that of a reference TaqMan-based real-time RT-PCR (trRT-PCR) assay for PDCoV. Of 149 swine small intestine, rectal swab, and serum samples, 71 and 75 tested positive for PDCoV according to RT-RAA-LFD and trRT-PCR, respectively. The diagnostic coincidence rate for both assays was 97.32% (145/149) and the kappa value was 0.946 (p < 0.001). Overall, the RT-RAA-LFD assay is a user-friendly diagnostic tool that can rapidly and visually detect PDCoV.